Childhood Obesity and Overweight Are Associated with Higher Risk of Perceived Stress and Poor Sleep Quality: A Cross-Sectional Study in Children Aged 6–9 Years - Maria Mentzelou; Aikaterini Louka; Theophanis Vorvolakos; Maria G. Kapetanou; Aspasia Seradri; George Antasouras; Christos Kontogiorgis; Georgia-Eirini Deligiannidou; Maria Chrysafi; Constantinos Giaginis (Metabolites)
Background/Objectives: The number of children with overweight and obesity is gradually increasing worldwide. This is an emergent public health problem as overweight and obesity persist through the next stages of human life, being associated with high risk of morbidity and mortality. In this respect, the purpose of the current cross-sectional survey is to explore whether the overweight/obesity of children aged 6–9 years may be related to the risk of developing perceived stress and poor sleep quality symptoms. Methods: This study recruited 4350 primary school children from diverse Greek rural and urban regions. The mothers of the enrolled children completed relevant questionnaires on children and maternal sociodemographics, anthropometric parameters, perinatal outcomes, breastfeeding practices, and lifestyle factors. The enrolled mothers also completed the Perceived Stress Scale (PSS) and the Pittsburgh Sleep Quality Index (PSQI) to evaluate the perceived stress and sleep quality of their matched children, respectively. Results: Our analysis reveals independently significant associations between diverse factors and children’s overweight/obesity such as child’s gender, family economic status, maternal gestational weight gain, childbirth weight, kind of delivery, exclusive breastfeeding, and children physical activity. Childhood overweight and obesity were independently associated with a more than three-fold higher risk of perceived stress and a more than two-fold higher likelihood of poor sleep quality after adjustment for multiple confounding factors. Conclusions: Obesity and overweight are related to enhanced risk of perceived stress and poor sleep quality in children aged 6–9 years. Public policies and dietary counseling interventions should be applied to inform new mothers about the harmful effects of childhood overweight/obesity and to direct them to adopt healthy dietary practices for their children.